Twenty First Century Approach to Traffic, Metro Police Officers Training Programs in South African - Kockott, Sean R (Universitas Malikussaleh, 2020)
This paper discusses, a systematic method for establishing and maintaining an effective training program that meets the requirements and expectations of road traffic law enforcers (Metropolitan Police and Traffic Officers) as per (South African Police Service Act 68 of 1995 & National Road Traffic Act 39 of 1996 and National Road Traffic Regulation, 2000). The systematic approach to road traffic law enforcers training includes a professional approach that is distinct, yet interrelated, in phases. These phases include analysis, design, development, implementation, and evaluation. Road traffic law enforcement training focus amongst other on outcome based training systems such as work integrated learning, performance-based training, training system development, instructional systems development, and other similar methods. For the purpose of this paper, theoretical and practical training are interchangeable. The systematic approach method may also be used in conjunction with other training organizations that contain road traffic safety professional training and qualification requirements.